Comparison of Effects of PELD and Fenestration in the Treatment of Geriatric Lumbar Lateral Recess Stenosis - Lv Z (Dove Medical Press, 2019)
Zhendong Lv,* Linyu Jin,* Kun Wang,* Zhi Chen, Fengning Li, Yuhui Zhang, Lifeng Lao, Chun Zhou, Xinfeng Li, Hongxing Shen Department of Spine Surgery, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinfeng Li; Hongxing Shen No. 160 Pujian Road, Shanghai 200127, People’s Republic of ChinaTel +86-18835991449; +86-13601814912Fax +86-021-58395057Email lxfrenji@126.com; shenhxgk@126.comPurpose: Although degenerative lumbar spinal stenosis (LSS) is increasingly being diagnosed in older people, there is much uncertainty about the appropriate operative treatment options. The objective of this study was to compare the outcome of percutaneous endoscopic lumbar decompression (PELD) versus fenestration for lumbar lateral recess stenosis (LRS) in geriatric patients over 75 years old.Materials and methods: This prospective controlled study was performed on 46 consecutive over aged patients with lateral recess stenosis who underwent either PELD or fenestration. Clinical data were recorded before, 1 week, 3 months and 1.5 years after surgery using visual analog scale (VAS), Japanese Orthopaedic Association Score (JOA), The Short-Form-36 (SF-36), and the modiﬁed Macnab evaluation criteria.Results: The patients’ mean age was 82.7 years (aged 75–93 years) in PELD group and 79.1 years (aged 75–88 years) in fenestration group. No statistical difference was found between PELD group and fenestration group with regards to VAS-back pain, VAS-leg pain, JOA and at 3 months and 1.5-year follow-up. However, the PELD group had a lower mean VAS for back pain at 1 week postoperatively (P<0.05). The quality of life in PELD group achieved the same remarkable improvement as fenestration group (P>0.05). Operative time (min) was similar between two groups (p>0.05), while the PELD techniques brought advantages in blood loss (mL) (48.3 vs 128.2, p<0.05), early ambulation (h) (5.5 vs 25.2, p<0.05), and anesthesia-related complications.Conclusion: Both PELD and fenestration showed favorable clinical outcomes for the treatment of lumbar lateral recess stenosis. In addition, PELD had advantages such as reduced traumatization and less anesthesia-related complications. In terms of quality of life and complications after operation, PELD under local anesthesia could be an efficient supplement to conventional decompression surgery in geriatric patients with lumbar lateral recess stenosis.Keywords: geriatric patients, lumbar lateral recess stenosis, percutaneous endoscopic lumbar decompression, PELD, minimally invasive